2014
DOI: 10.1021/ja5064795
|View full text |Cite
|
Sign up to set email alerts
|

Polar Interactions Trump Hydrophobicity in Stabilizing the Self-Inserting Membrane Protein Mistic

Abstract: Canonical integral membrane proteins are attached to lipid bilayers through hydrophobic transmembrane helices, whose topogenesis requires sophisticated insertion machineries. By contrast, membrane proteins that, for evolutionary or functional reasons, cannot rely on these machineries need to resort to driving forces other than hydrophobicity. A striking example is the self-inserting Bacillus subtilis protein Mistic, which is involved in biofilm formation and has found application as a fusion tag supporting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(66 citation statements)
references
References 70 publications
11
54
1
Order By: Relevance
“…Best-fit parameter values and associated 95% confidence intervals are given in Table 2 interactions between the peptide moiety of myr-Src and lipid headgroups, which are not accounted for by GouyChapman theory. For instance, it has been reported that, in addition to purely Coulombic interactions, polar and charged residues can interact with lipid headgroups by monopoledipole and dipole-dipole or, more generally, multipolar contacts (44,45). In the present case, such a scenario excluding major changes regarding the myristoyl chain of myr-Src is supported by NMR data, because its geometric parameters are not noticeably affected by the introduction of DLPS ( Fig.…”
Section: Binding To Dmpc Membranessupporting
confidence: 75%
“…Best-fit parameter values and associated 95% confidence intervals are given in Table 2 interactions between the peptide moiety of myr-Src and lipid headgroups, which are not accounted for by GouyChapman theory. For instance, it has been reported that, in addition to purely Coulombic interactions, polar and charged residues can interact with lipid headgroups by monopoledipole and dipole-dipole or, more generally, multipolar contacts (44,45). In the present case, such a scenario excluding major changes regarding the myristoyl chain of myr-Src is supported by NMR data, because its geometric parameters are not noticeably affected by the introduction of DLPS ( Fig.…”
Section: Binding To Dmpc Membranessupporting
confidence: 75%
“…The present results show that, although the isolated A3 peptide retains its high affinity for LDAO observed in the context of the full‐length protein, H3 or A3 alone interact with lipid membranes neither in vivo nor in vitro , respectively. In fact, the invariant ∼30% helical content of A3 in the presence of various lipids is virtually identical to what has been found for the H3 segment of urea‐unfolded full‐length Mistic in the absence of any membrane‐mimetic system and only about half the average helicity of the native protein in different detergent micelles …”
Section: Discussionsupporting
confidence: 80%
“…), whereas values for transmembrane insertion were generally unfavorable. Surprisingly, structural studies have pointed out that most of the residues involved in binding the zwitterionic detergent LDAO are located in H3 and H4, which renders LDAO‐solubilized Mistic extremely stable against denaturant‐induced unfolding . The present results show that, although the isolated A3 peptide retains its high affinity for LDAO observed in the context of the full‐length protein, H3 or A3 alone interact with lipid membranes neither in vivo nor in vitro , respectively.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations